Elucidation of the liver pathophysiology of COVID-19 patients using liver-on-a-chips. Issue 3 (7th March 2023) - Deguchi, Sayaka; Kosugi, Kaori; Hashimoto, Rina; Sakamoto, Ayaka; Yamamoto, Masaki; Krol, Rafal P; Gee, Peter; Negoro, Ryosuke; Noda, Takeshi; Yamamoto, Takuya; Torisawa, Yu-suke; Nagao, Miki; et al.
Abstract: SARS-CoV-2 induces severe organ damage not only in the lung but also in the liver, heart, kidney, and intestine. It is known that COVID-19 severity correlates with liver dysfunction, but few studies have investigated the liver pathophysiology in COVID-19 patients. Here, we elucidated liver pathophysiology in COVID-19 patients using organs-on-a-chip technology and clinical analyses. First, we developed liver-on-a-chip (LoC) which recapitulating hepatic functions around the intrahepatic bile duct and blood vessel. We found that hepatic dysfunctions, but not hepatobiliary diseases, were strongly induced by SARS-CoV-2 infection. Next, we evaluated the therapeutic effects of COVID-19 drugs to inhibit viral replication and recover hepatic dysfunctions, and found that the combination of anti-viral and immunosuppressive drugs (Remdesivir and Baricitinib) is effective to treat hepatic dysfunctions caused by SARS-CoV-2 infection. Finally, we analyzed the sera obtained from COVID-19 patients, and revealed that COVID-19 patients, who were positive for serum viral RNA, are likely to become severe and develop hepatic dysfunctions, as compared with COVID-19 patients who were negative for serum viral RNA. We succeeded in modeling the liver pathophysiology of COVID-19 patients using LoC technology and clinical samples.